Teachers’ Intervention in School Bullying: A Qualitative Analysis on Italian Teachers - Acquadro Maran, Daniela; Tirassa, Maurizio; Begotti, Tatiana (Frontiers in Education, 2017)
The chances that a teacher will intervene in a case of bullying appear to be associated with several variables, which may be resumed as the confidence that he has in his capability to deal with problems at school. In accordance with Social Cognitive Theory and Attribution Theory, the three-factor model of self-confidence was used to investigate the differences between preservice teachers (PSTs) and in service teachers (ISTs). A qualitative approach was used to examine the strategies of intervention suggested against bullying at school by teachers. Results showed that there are different profiles to PSTs and ISTs. In both groups, participants with low outcome expectations (OEs) revealed a propension to intervention in the classroom, while those characterized by high external locus of control tend to intervene only upon the victims and the bullies. ISTs with high OEs are the group most likely to intervene directly, because they are self-confident in their abilities to put an end to the problem. Overall, the data show that professional experience is important for the interpretation of the phenomenon and remedies suggested. This does not mean that interventions suggested by IST are necessarily effective, but that they tend to have a stronger sense of self-efficacy.